2017
DOI: 10.1007/s11682-017-9747-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidental findings on cerebral MRI in twins: the Older Australian Twins Study

Abstract: Incidental findings on structural cerebral magnetic resonance imaging (MRI) are common in healthy subjects, and the prevalence increases with age. There is a paucity of data regarding incidental cerebral findings in twins. We examined brain MRI data acquired from community-dwelling older twins to determine the prevalence and concordance of incidental cerebral findings, as well as the associated clinical implications. Participants (n = 400) were drawn from the Older Australian Twins Study. T1-weighted and T2-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…While we expect the quality of neuroimaging at our comprehensive epilepsy center to be higher than a non-specialized center, this limited data quality matches what is often available clinically. Additionally, when compared to the aforementioned studies of MRI findings in patients without seizures [15,[18][19][20][21][22][23][24], a higher proportion of our images were obtained on 3 Tesla scanners, and many were obtained with the specialized epilepsy-protocol. While we did not observe increased rates of EAF or ERF with these higher quality images in patients with functional seizures, our elevated rate of incidental and nonspecific findings may be attributed to these differences in quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we expect the quality of neuroimaging at our comprehensive epilepsy center to be higher than a non-specialized center, this limited data quality matches what is often available clinically. Additionally, when compared to the aforementioned studies of MRI findings in patients without seizures [15,[18][19][20][21][22][23][24], a higher proportion of our images were obtained on 3 Tesla scanners, and many were obtained with the specialized epilepsy-protocol. While we did not observe increased rates of EAF or ERF with these higher quality images in patients with functional seizures, our elevated rate of incidental and nonspecific findings may be attributed to these differences in quality.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of these abnormalities were nonspecific, two previous studies found that 5-10% of them had definitive epilepsy-associated findings (EAF) including hippocampal sclerosis [7,10]. This rate of nonspecific abnormalities is markedly higher than healthy controls, who typically have nonspecific findings on 2-18% of MRIs, with the rate of EAF being too low to quantify reliably [15][16][17][18][19][20][21][22][23][24]. In the years following most of these prior studies, the development of epilepsy-specific scanning protocols and widespread adoption of 3 Tesla scanners have led to higher image quality and sensitivity for subtle abnormalities [8,25].…”
mentioning
confidence: 99%
“…19 Heritability (variation explained by the genome) estimates lie between 0.49 and 0.83 for ophthalmologic vascular parameters [20][21][22][23] and between 0.64 and 0.77 for small vessel disease. [24][25][26][27] By performing a study on monozygotic twins, we aimed to elucidate the genetic and environmental influence on possible relationships between these two vascular systems. For this purpose, two sets of analyses will be performed; a cross-twin cross trait and a twindifference analysis.…”
mentioning
confidence: 99%
“…Magnet strength and sequence differed between studies. The most frequently used strengths were 1.0 T [ 57 , 70 , 77 ], 1.5 T [ 9 , 10 , 14 , 26 , 31 , 44 , 51 , 64 , 65 , 68 , 71 , 72 , 81 ], and 3.0 T [ 3 , 12 , 25 , 28 , 29 , 40 , 42 , 48 , 49 , 76 ], while some studies used more than one strength (1.5 T and 3 T) [ 15 , 41 , 43 , 52 , 62 ]. Imaging scans were read by senior radiologists and/or neuroradiologists and/or neurologists in a large number of the included studies [ 3 , 12 , 14 , 15 , 28 , 40 – 43 , 48 , 49 , 52 , 60 , 68 , 71 , 72 , 76 , 77 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study [ 9 ] had no radiologist, neuroradiologist, or neurologist in the team reading the scans; their team included researchers with a doctor of medicine training in neuropsychology. T1-weighted image (T1WI) [ 25 , 28 ], T2-weighted image (T2WI) and fluid-attenuated inversion recovery (FLAIR)[ 57 ] were the most commonly used MRI sequences, either alone or combined [ 3 , 9 , 10 , 12 , 14 , 15 , 26 , 31 , 40 42 , 44 , 48 , 49 , 52 , 62 , 65 , 68 , 71 , 72 , 76 , 77 , 81 ]. Other sequences that were used in a smaller number of published papers were gradient recalled echo T2WI (GRE T2WI) [ 12 , 14 , 48 , 72 , 77 ], proton density weighted imaging (PDWI) [ 48 ], perfusion weighted imaging (PWI) [ 48 ], diffusion tensor imaging (DTI) [ 48 ], time-of-flight (TOF) [ 48 ] angiography and T1/T2 spine echo (SE) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%